1998
DOI: 10.1023/a:1006879820805
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Se is an essential trace element and is found as a selenocysteine in the active site of Se-enzymes, such as glutathione peroxidase. tRNASec is first aminoacylated with serine by Ser RS and further is converted to selenocysteyl-tRNA by selenocysteine synthase. Mammalian selenocysteine tRNA has dual identities with Ser RS and selenocysteine synthase. Key identity elements for selenocysteine synthase are the long 9 bp AA- and long 6 bp D-stems. Major serine tRNA was converted to a mutant with a 9 bp AA-stem and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…In addition, SerRS also recognizes not only (7/5) tRNA Ser but also (8/5, 9/4 and 8/4) tRNA Sec and even a variant of tRNA Sec with a 9/3 structure (37). SelC* tRNAs were named after the selC gene, which encodes tRNA Sec in E. coli .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, SerRS also recognizes not only (7/5) tRNA Ser but also (8/5, 9/4 and 8/4) tRNA Sec and even a variant of tRNA Sec with a 9/3 structure (37). SelC* tRNAs were named after the selC gene, which encodes tRNA Sec in E. coli .…”
Section: Resultsmentioning
confidence: 99%
“…As predicted, the two G-1 tRNA1 species were aminoacylated by E. coli HisRS, even more efficiently than E. coli tRNA His , despite the Thr GGU anticodon (Figure 4B). The GUG triplet at positions 35–37 (but not the anticodon positions 34–36 in tRNA His ) of the two G-1 tRNA1 species might have been recognized by HisRS (3537). Interestingly, the two G-1 tRNA1 species did not insert His in response to the ACC Thr codon at position 2 in a sfGFP variant gene in E. coli .…”
Section: Resultsmentioning
confidence: 99%
“…To test for possible "overfitting" of that kind, we examined the noncanonical amino acids selenocysteine (Sec) and pyrrolysine (Pyl). Both amino acids are incorporated into proteins by codon dependent translation, co-opting either a stop codon (Pyl; UAG 31,32 ) or a redundant and rarely used serine codon (Sec; AGU [33][34][35] ) to enlarge the genetic code. These noncanonical amino acids involve changes in both the cognate tRNAs and the enzymes that recognize them.…”
Section: Cross-validationmentioning
confidence: 99%
“…This suggests an influence of base specificity on the tRNA Sec and/or the involvement of the orientation of the V‐arm. We also showed that the 4 bp T‐stem of the tRNA Sec is not important for selenylation, because tRNA Sec mutants having 3, 4 or 5 bp T‐stems still possessed selenylation activity [14]. The length of the coaxial helix (domain II) formed by the stacking of the AA and T‐stems is essential for serylation, because tRNA Sec having 12 or 13 bp of domain II were still active, but not the mutants carrying 11 or 14 bp of domain II.…”
Section: Introductionmentioning
confidence: 72%
“…We succeeded in the conversion of tRNA Ser to tRNA Sec , but the selenylation activity was weak and about 1/20 of that of the native tRNA Sec [14]. This suggests an influence of base specificity on the tRNA Sec and/or the involvement of the orientation of the V‐arm.…”
Section: Introductionmentioning
confidence: 94%